Avaliação da implantação de um protocolo gerenciado de sepse em um hospital pediátrico - Santos, Gustavo Rodrigues dos (2019)
Sepsis is characterized by an infectious condition associated with organic dysfunctions, with high morbidity and mortality, with an increasing incidence. Since 2004, medical societies have been meeting to build sepsis treatment guidelines. The aim of this study was to evaluate the impact of the implementation of a managed sepsis guideline in a pediatric hospital. It is a retrospective cohort study, that analyzed patients with sepsis during their hospital stay, before and after the implementation of the sepsis diagnosis and management guidelines. Several quality improvement interventions were established for the implementation of the guideline, aiming to improve the recognition of sepsis and adherence to the three components of the first hour bundle: administration of antibiotics; fluid administration; blood culture before antibiotic. Adherence to the measurements was studied in the pre- and post-implementation periods of the guideline (intervention), as well as the impact of this adherence on the outcome of sepsis cases. The study included 187 patients: 84 in the pre-intervention period and 103 in the post-intervention. After the intervention we observed an increase in the recognition of sepsis (OR: 21.5 [95% CI: 10.12-45.66]) and an improve of compliance to the first-hour bundle (61.6% [against 0% before]), as well as in each measure of the bundle. The risk of death in the pre-intervention was higher than in the post-intervention (RR: 4.09 [95% CI: 1.16-14.38]). This study showed that the implementation of a sepsis managed guideline, accompanied by quality improvement interventions was able to improve adherence to the care measures and to reduce sepsis mortality.